PENGARUH INTENSITAS CAHAYA DAN SPEKTRUM CAHAYA TAMPAK TERHADAP PERTUMBUHAN UDANG PUTIH (LITOPENAEUSVANNAMEI) DITINJAU DARI SEGI HUBUNGAN PANJANG DAN BERAT - Sudra Irawan, Didik Setyawarno, dan Watini (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research aims at firstly knowing the influence of light intensity and visible lightspectrum on the equation of the length and weight of the white prawn (VannameiLitopenaeus) looked after at the fishpond with intensive fully plastic conducting system andwith semi plastic based fishpond. Secondly, comparing the result of data analysis by 2 differentmethods - Weighted Regression Method (Carlander, 1968 in Effendie, 1997) and Least SquareMethod or Smallest Method Square (Sudjana, 1992). Thirdly, knowing the factor value ofCondition K(Tl) or of Condition Factor ( CF) in this researchIn this research there are 14 ( fourteen) fishponds. The method used is a case studymethod. In collecting the data there are two procedures which were executed. They are theprocedure of collecting the sample of prawn and the procedure of measuring the weightand length of the white prawn bodyThe results of the research are (1) there is an influence of light intensity and visible lightspectrum on the length and body weight of the white prawn looked after at fishpond withintensive fully plastic conducting system and semi plastic based fishpond, (2) the result ofthe data analysis by using 2 different methods indicate that semi plastic fishpond of 40 whiteprawn seed with lighting of 40 watt lamp has been compared to the highest growth level,the level of another fishpond, (3) the biggest condition factor is pool E.2 (semi plastic fishpondwith 40 white prawns with the lighting of 40 watt lamp.Keyword: Light intensity, light spectrum, and heavy and long relationship